2022
DOI: 10.1177/15579883221120987
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitating Factors to HIV Treatment Among Men in a High-HIV-Burdened District in KwaZulu-Natal, South Africa: A Qualitative Study

Abstract: Despite enormous increases in the proportion of people living with HIV accessing treatment in sub-Saharan Africa, major gender disparities persist, with men experiencing lower rates of testing, linkage to treatment, and retention in care. In this study, we investigated the barriers and facilitating factors to HIV treatment among men in uThukela, a high-HIV-burdened district in KwaZulu-Natal province, South Africa. We conducted a qualitative study including nine Black African male participants who were recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
0
10
1
Order By: Relevance
“…Timely and substantial linkage to HIV treatment among men newly diagnosed with HIV is critical to improve health outcomes and maximize population-level benefits from ART. Despite the well documented barriers deterring men from accessing health services in SSA [ 4 , 18 ], our study findings showed higher rates of linkage to care compared to findings from similar settings in KwaZulu-Natal and in Western Cape provinces [ 19 , 20 ]. A household-based community cross-sectional survey conducted in KwaZulu-Natal province found that 71% (95% CI: 68.6–73.4) of participants were linked to care, accounting for 74% (95% CI: 71.6–76.9) among women and 60% (95% CI: 54.2–66.1) among men [ 19 ].…”
Section: Discussioncontrasting
confidence: 92%
“…Timely and substantial linkage to HIV treatment among men newly diagnosed with HIV is critical to improve health outcomes and maximize population-level benefits from ART. Despite the well documented barriers deterring men from accessing health services in SSA [ 4 , 18 ], our study findings showed higher rates of linkage to care compared to findings from similar settings in KwaZulu-Natal and in Western Cape provinces [ 19 , 20 ]. A household-based community cross-sectional survey conducted in KwaZulu-Natal province found that 71% (95% CI: 68.6–73.4) of participants were linked to care, accounting for 74% (95% CI: 71.6–76.9) among women and 60% (95% CI: 54.2–66.1) among men [ 19 ].…”
Section: Discussioncontrasting
confidence: 92%
“…21,23 A study in KwaZulu-Natal also reported insufficient time or the need to prioritize going to work as barriers for linking to care among men. 24 In this study, of those who were not linked to care in 1 month, >60% could not be reached or did not consent for EPIC-HIV 2. The primary reasons included being busy at work or feeling fine, which were similar to the barriers to linkage to care found in other studies.…”
Section: Discussionmentioning
confidence: 73%
“…Although our results reveal a higher proportion of detectable HIV VL records from female patients, it is possible that this could be a bias of the demographics of the population accessing HIV care, and not necessarily an indication that more women are viraemic on ART. This in part could be associated with poor retention in HIV care among males as reported by the UNAIDS and as shown by studies from other African countries, including South Africa [ 55 , 56 ]. Lastly, there is a need to prospectively assess longitudinal geospatial trends of VLs to assess whether the hotspots of VLs observed were the impact of the pandemic that settles over time as the health system recovers from the impact of COVID-19 pandemic, or whether this is a concerning trend that becomes sustained or worse over time.…”
Section: Discussionmentioning
confidence: 97%